2011
DOI: 10.1017/s0022149x1100040x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of water and humidity on the hatching of Nematodirus battus eggs

Abstract: This paper examines the influence of water on the ecology of the eggs of Nematodirus battus, with a view to estimating the importance of including rainfall in mathematical models of parasite abundance. The literature suggests that, under pasture conditions, the availability of moisture is unlikely to be limiting for egg development, while eggs and infective larvae are highly resistant to desiccation. In the presented experiment, eggs that had been kept in salt sludges at 95% and 70% RH and were subsequently pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A threshold-based model to predict the spatio-temporal variation in hatching dates of N. battus was developed based on conclusive experimental evidence that N. battus eggs require 7 days of experience between the lower and upper threshold temperatures of 11·5 and 17 °C to hatch, and that fluctuations outside of this range suspend hatching (Van Dijk and Morgan, 2008). Subsequent results on effects of humidity on hatching confirmed that temperature acts as the main driver of larval availability (Van Dijk and Morgan, 2012). Each 24 h period in which minimum ( T min ) and maximum ( T max ) temperatures were both within the hatching range of 11·5–17 °C counted as one full hatching day.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…A threshold-based model to predict the spatio-temporal variation in hatching dates of N. battus was developed based on conclusive experimental evidence that N. battus eggs require 7 days of experience between the lower and upper threshold temperatures of 11·5 and 17 °C to hatch, and that fluctuations outside of this range suspend hatching (Van Dijk and Morgan, 2008). Subsequent results on effects of humidity on hatching confirmed that temperature acts as the main driver of larval availability (Van Dijk and Morgan, 2012). Each 24 h period in which minimum ( T min ) and maximum ( T max ) temperatures were both within the hatching range of 11·5–17 °C counted as one full hatching day.…”
Section: Methodsmentioning
confidence: 84%
“…Thus, warmer temperatures favoured increased production of infective stages of gastrointestinal nematodes of rabbits, but not necessarily higher infection levels in the host, suggesting that the way in which hosts interact with available infective stages is crucial to net effects of climate change on infection (Hernandez et al 2013). In a trematode-snail-amphibian system, striking non-linearities in the effects of climate warming were observed (Paull et al 2012; Paull and Johnson, 2014). Higher temperatures led to earlier infective stage emergence, but decreased overlap between parasite and host presence, and consequently a marked decrease in infection levels and pathology (Paull and Johnson, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Spring remained the most prevalent time for N. battus disease across the UK 16,25 ; however, respondents from the south reported additional infections throughout the year, including autumn and winter, while N. battus appeared to be restricted to spring/summer in the north. The lifecycle of parasitic nematodes, particularly the timing of hatching and survivability of larval stages on pasture, are intrinsically linked with environmental conditions which could explain the variation reported in timing of disease [26][27][28] ; however, significant differences in management practices are likely to have contributed to the variation observed.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the parasite population brought about by changes in environmental/climatic conditions leading to changes in human behaviour, land use and/or animal husbandry [ 63 - 65 ] could be involved. Changes in climate have been shown to lead to conditions favourable for longer grazing periods [ 66 ].…”
Section: Discussionmentioning
confidence: 99%